The influence of the Eisenia fetida holding environment on medicinal leech breeding - Aminov, R. F. (Acta Biologica Ukrainica, 2025)
The study used 120 medicinal leeches, including 80 Hirudo verbana and 40 Hirudo orientalis. Four groups of animals were formed: two control and two experimental. The control groups consisted of medicinal leeches of both species, which were kept using the modern jar method. Experimental scheme. Control group: a peat-soil weakly acidic environment (pH 5.5) was prepared. As fertilization belts formed in leeches, they were transplanted into 3-litre sterile containers filled with the moist peat-soil medium. Afterwards, the containers were covered with a fabric that allowed for full oxygen permeability. The containers with the animals were placed in a dark room with a temperature of +25-26 °C and diffused artificial lighting. After a month, parent leeches and soft cocoons were collected. Juveniles were then selected from the cocoons and placed in sterile 3-litre containers filled with settled tap water. Experimental groups: instead of the peat-soil environment, medical leeches were placed in an environment selected from the Eisenia fetida (pH 5.0). All other manipulations were performed as in the control group. In the control group, animals in the peat-soil environment exhibited good health, with low mortality rates (Hirudo verbana 2.2±0.2% and Hirudo orientalis 1.9±0.2%) and high fecundity (Hirudo verbana 9.2±0.3% and Hirudo orientalis 6.1±0.2%), indicating the suitability of the maintenance environment p < 0.05. The experimental group yielded negative results, reflected in significantly higher mortality rates for both species: Hirudo verbana 75.2±4.2% and Hirudo orientalis 80±3.1%, p < 0.05). Furthermore, in the experimental groups, most animals produced few or no cocoons and offspring (Hirudo verbana 0.9±0.05%). A significant proportion of the cocoons were defective: Hirudo verbana 55.3±3.4% (p < 0.05). Fertile cocoons contained a limited number of offspring.